UJI APLIKASI POC KEONG MAS DAN PUPUK SP-36 TERHADAP PERTUMBUHAN SERTA P RODUKSI TANAMAN TOMAT CERI (Solanum lycopesicum var. cerasiforme) - Suratman; T Rosmawaty (DINAMIKA PERTANIAN, 2022)
This study aimed to determine the effect of the main and main POC of golden snail and SP-36 fertilizer on the growth and production of cherry tomatoes (Solanum lycopersicum var. cerasiforme). This research was carried out in the experimental farm of the Faculty of Agriculture, Riau Islamic University, Jalan Kaharuddin Nasution No. 113, Air Cold Village, Bukit Raya District, Pekanbaru City. This research was carried out for 5 months starting from February to June 2021. This study used a completely randomized design (CRD) with 2 factorials, the first factor was POC Keong Mas (P) and the second factor was SP-36 fertilizer (S) each consisting of 4 levels of treatment. The parameters observed were: plant height, flowering age, number of bunches planted, harvest age, the weight of fruit planted, the weight of fruit per fruit, number of fruit planted, and number of leftover fruit. The research data were analyzed statistically and continued with the BNJ test at the 5% level. The results showed that the effect of the POC of golden snail and SP-36 fertilizer had a significant effect on all observation parameters. The best treatment was giving a combination of POC of golden snail 75 ml/L of water and SP-36 fertilizer of 7.5 g/plant (P3S3). The main effect of giving golden snail POC gave a significant effect on all observation parameters. The best treatment was giving the golden snail POC 75 ml/L water (P3). The main effect of SP-36 fertilizer had a significant effect on all observation parameters. The best treatment was the application of SP-36 7.5 g/plant (S3) fertilizer.